Examining the Effects of the Oral Supplement Biota orientalis in the Osteochondral Fragment-Exercise Model of Osteoarthritis in the Horse - Seabaugh, Kathryn A.; Barrett, Myra F.; Rao, Sangeeta; McIlwraith, C. Wayne; Frisbie, David D. (Frontiers in Veterinary Science, 2022)
Osteoarthritis (OA) is a common problem in horses. Several oral supplements have been proposed as treatments for horses with OA. The object of this study was to evaluate the use of the oil extract from the seeds of Biota orientalis (BO) for the treatment of experimentally induced OA in horses. OA was induced in 16, 2–5 year old horses in one middle carpal joint on Day 0; the other limb underwent a sham operation. Once daily oral treatment with BO or placebo was initiated on Day 0 and continued to Day 70. All horses were exercised 5 days a week starting on Day 14 through Day 70. The horses were evaluated every other week for lameness and serum GAG concentration as well as weekly synovial fluid assessment. Magnetic resonance imaging was performed on Day 7 and 70. Radiographic changes were assessed on Day 0, 14, and 70. On Day 70 tissue from the middle carpal joint was assessed macroscopically and histologically. All outcome parameters were compared between treatment groups to identify effects of treatment. Compared to placebo a significant decrease was found in synovial fluid prostaglandin E2 concentration and white blood cell counts in horses treated with BO. There was a significant reduction in radiographic scores for subchondral lysis of the radial carpal bone, osteophyte formation, subchondral sclerosis of the radial carpal bone, and total radiographic score for the horses treated with BO. There was no significant difference between treatment groups in clinical lameness findings, MRI findings, macroscopic grading or histologic grading. This study suggests a significant anti-inflammatory effect from oral BO that should be further investigated in clinical OA.